2016
DOI: 10.1007/s10529-016-2112-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of chlorogenic acid and its analogues as inhibitors: an investigation of the inhibition of sortase A of Staphylococcus aureus using molecular docking and dynamic simulation

Abstract: The mechanism obtained by molecular dynamics simulation is thus useful for the development of novel, selective SrtA inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Five other hydroxycinnamic acids-caffeic acid, neochlorogenic caid, cryptochlorogenic acid, and ferulic and isoferulic acids-were also identified as potent inhibitors of this Gram-positive bacteria transpeptidase. Chlorogenic acid exhibited the best sortase-inhibitory activity with an IC 50 of 34 µg/mL, followed by caffeic acid (IC 50 155 µg/mL), ferulic acid (IC 50 257 µg/mL), and neo-and cryptochlorogenic acids with IC 50 values of 300 µg/mL [53]. All three chlorogenic acids were identified in both V. opulus fruit and bark extracts, while caffeic acid was only present in fruit extracts (Table S1 in Supplementary Materials).…”
Section: Discussionmentioning
confidence: 99%
“…Five other hydroxycinnamic acids-caffeic acid, neochlorogenic caid, cryptochlorogenic acid, and ferulic and isoferulic acids-were also identified as potent inhibitors of this Gram-positive bacteria transpeptidase. Chlorogenic acid exhibited the best sortase-inhibitory activity with an IC 50 of 34 µg/mL, followed by caffeic acid (IC 50 155 µg/mL), ferulic acid (IC 50 257 µg/mL), and neo-and cryptochlorogenic acids with IC 50 values of 300 µg/mL [53]. All three chlorogenic acids were identified in both V. opulus fruit and bark extracts, while caffeic acid was only present in fruit extracts (Table S1 in Supplementary Materials).…”
Section: Discussionmentioning
confidence: 99%
“…The 3- O -methylated derivate of caffeic acid, the ferulic acid produced a low inhibitory effect on SrtA, with an IC 50 over 100 μM [ 40 ]. Its isomer, 4- O -methylated derivate, the isoferulic acid was tested against SrtAΔN59 with a low effect, the measured IC 50 being over 500 μM [ 41 ].…”
Section: Sortase a Inhibitorsmentioning
confidence: 99%
“…Two isomers of the chlorogenic acid, cryptochlorogenic acid (4- O -caffeoylquinic acid) and neochlorogenic acid (5- O -caffeoylquinic acid), were tested against SrtAΔN59. Both isomers exhibited an IC 50 over 500 μM, highlighting the importance of the functional groups’ reciprocal positions [ 41 ].…”
Section: Sortase a Inhibitorsmentioning
confidence: 99%
“…Previous studies have demonstrated that many SrtA inhibitors could interact with Arg197 residue which was recognized as one of the residues of active site triad of S. aureus SrtA. 22,38,40,41 Substitution of Arg197 residue results in complete loss of catalytic activity of SrtA, 42 thus the two strong hydrogen bonds between Arg197 and CHQA might affect the activity of SrtA. Therefore, it was suggested that CHQA inhibited the enzymatic activity of S. aureus SrtA through binding to the active region via non-covalent interactions.…”
Section: Chqa Reduced S Aureus Adhesion To Brinogenmentioning
confidence: 99%
“…12 Plant secondary metabolites are main sources of antibacterial and antibiolm agents. Numerous polyphenols have been demonstrated to signicantly inhibit the biolm formation of pathogens, 19,20 and many of them showed a potent inhibitory activity against SrtA of S. aureus, such as morin, myricetin, quercetin, 21 chlorogenic acid, 22 kaempferol, 10 and isovitexin. 23 Previously, we have reported a novel phenolic compound, 3-ptrans-coumaroyl-2-hydroxyquinic acid (CHQA, Fig.…”
Section: Introductionmentioning
confidence: 99%